Effect of the type of environmental stress on the emergence of sunflower (Helianthus annus L.), soybean (Glycine max (L.) Merril) and maize (Zea mays L.) seeds with different levels of vigor - De Figueiredo E Albuquerque, M. C.; De Carvalho, N. M. [UNESP] (International Seed Testing Association, 2003)
Sowing is a critical time in the cycle of a crop and the seeds are frequently exposed to adverse conditions that may compromise the establishment of seedlings in the field. On this basis, the objective of the present study was to determine the effect of types of environmental stress on the emergence of sunflower, maize and soybean seeds with different levels of vigor. High vigor seeds were artificially aged in order to obtain medium and low vigor seeds and then they were sown in clay soil in plastic boxes and submitted to the following types of environmental stress during the germination process : 1) high temperature (35°C), 2) low temperature (15 or 18°C), 3) water excess (Ψ > -0.0001 MPa), 4) water deficiency (Ψ approximately equal to -1.1; -1.2 and -0.6 MPa for sunflower, maize and soybean, respectively), 5) sowing at a depth of 7 cm and 6) pathogenic infection of sunflower seeds with Alternaria helianthi, of maize seeds with Fusarium moniliforme and of soybean seeds with Colletotrichum dematium, var. truncata. The results were compared to those obtained with controls sown under optimal condition. It was concluded that: 1) the effect of seed vigor on emergence depends on the type of enviromental stress to which the seeds are exposed, 2) the stress to which the the seeds demonstrated highest sensitivity varied with species and 3) high temperature stress was the one that most impaired the emergence of the three species.